Ortho-vanillin derived Al(iii) and Co(iii) catalyst systems for switchable catalysis using ε-decalactone, phthalic anhydride and cyclohexene oxide. Issue 5 (12th January 2021) - Diment, Wilfred T.; Stößer, Tim; Kerr, Ryan W. F.; Phanopoulos, Andreas; Durr, Christopher B.; Williams, Charlotte K.
Abstract : Switchable catalysis is a useful one-pot method to prepare block polyesters utilising a single catalyst exposed to a mixture of monomers. Abstract : Switchable catalysis is a useful one-pot method to prepare block polyesters utilising a single catalyst exposed to a mixture of monomers. The catalyst is switched between lactone ring-opening polymerization (ROP) and epoxide/anhydride ring-opening copolymerization (ROCOP) by controlling its chain-end chemistry. Here, novel aluminium(iii ) (1 ) and cobalt(iii ) complexes (2 ), coordinated by ortho -vanillin derived salen ligands, show excellent switchable catalytic activity and selectivity for the preparation of poly(ε-decalactone- block -cyclohexene phthalate- block -ε-decalactone) [PDL- b -PCHPE- b -PDL]. Both complexes have competitive activities with a commercial chromium salen catalyst for epoxide/anhydride ROCOP (TOFCr(III) = 1200 h −1 vs. TOFAl(III) = 350 h −1, 1 mol% catalyst loading vs. anhydride, 100 °C) and are significantly more active than the commercial catalyst for lactone ROP (TOFcr(III) = 3 h −1 vs. TOFAl(III) = 300 h −1 ; 0.5 mol% catalyst loading vs. lactone, T = 100 °C). The catalysts are tolerant to low loadings (0.1 mol% vs. anhydride, 0.05% vs. lactone) and produce high molar mass triblock polyesters ( M n = 6–57 kg mol −1 ). The efficient production of high molar mass polyesters allows for future optimization of the block polyester thermal–mechanical properties and applications.